Physical exercise training interventions for children and young adults during and after treatment for childhood cancer - Braam, Katja I (Cochrane Database Syst Rev, 2016)
BACKGROUND: A decreased physical fitness has been reported in patients and survivors of childhood cancer. This is influenced by the negative effects of the disease and the treatment of childhood cancer. Exercise training for adult cancer patients has frequently been reported to improve physical fitness. In recent years, literature on this subject has also become available for children and young adults with cancer, both during and after treatment. This is an update of the original review that was performed in 2011. OBJECTIVES: To evaluate the effect of a physical exercise training intervention on the physical fitness (i.e. aerobic capacity, muscle strength, or functional performance) of children with cancer within the first five years from their diagnosis (performed either during or after cancer treatment), compared to a control group of children with cancer who did not receive an exercise intervention. To determine whether physical exercise within the first five years of diagnosis has an effect on fatigue, anxiety, depression, self efficacy, and HRQoL and to determine whether there are any adverse effects of the intervention. SEARCH METHODS: We searched the electronic databases of Cochrane Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, CINAHL, and PEDro; ongoing trial registries and conference proceedings on 6 September 2011 and 11 November 2014. In addition, we performed a handsearch of reference lists. SELECTION CRITERIA: The review included randomized controlled trials (RCTs) and clinical controlled trials (CCTs) that compared the effects of physical exercise training with no training, in people who were within the first five years of their diagnosis of childhood cancer. DATA COLLECTION AND ANALYSIS: Two review authors independently identified studies meeting the inclusion criteria, performed the data extraction, and assessed the risk of bias using standardized forms. Study quality was rated by the Grading of Recommendation Assessment, Development and Evaluation (GRADE) criteria. MAIN RESULTS: Apart from the five studies in the original review, this update included one additional RCT. In total, the analysis included 171 participants, all during treatment for childhood acute lymphoblastic leukaemia (ALL). The duration of the training sessions ranged from 15 to 60 minutes per session. Both the type of intervention and intervention period varied in all the included studies. However, the control group always received usual care. All studies had methodological limitations, such as small numbers of participants, unclear randomization methods, and single‐blind study designs in case of one RCT and all results were of moderate to very low quality (GRADE). Cardiorespiratory fitness was evaluated by the 9‐minute run‐walk test, timed up‐and‐down stairs test, the timed up‐and‐go time test, and the 20‐m shuttle run test. Data of the 9‐minute run‐walk test and the timed up‐and‐down stairs test could be pooled. The combined 9‐minute run‐walk test results showed significant differences between the intervention and the control groups, in favour of the intervention group (standardized mean difference (SMD) 0.69; 95% confidence interval (CI) 0.02 to 1.35). Pooled data from the timed up‐and‐down stairs test showed no significant differences in cardiorespiratory fitness (SMD ‐0.54; 95% CI ‐1.77 to 0.70). However, there was considerable heterogeneity (I(2) = 84%) between the two studies on this outcome. The other two single‐study outcomes, 20‐m shuttle run test and the timed up‐and‐go test, also showed positive results for cardiorespiratory fitness in favour of the intervention group. Only one study assessed the effect of exercise on bone mineral density (total body), showing a statistically significant positive intervention effect (SMD 1.07; 95% CI 0.48 to 1.66). The pooled data on body mass index showed no statistically significant end‐score difference between the intervention and control group (SMD 0.59; 95% CI ‐0.23 to 1.41). Three studies assessed flexibility. Two studies assessed ankle dorsiflexion. One study assessed active ankle dorsiflexion, while the other assessed passive ankle dorsiflexion. There were no statistically significant differences between the intervention and control group with the active ankle dorsiflexion test; however, in favour of the intervention group, they were found for passive ankle dorsiflexion (SMD 0.69; 95% CI 0.12 to 1.25). The third study assessed body flexibility using the sit‐and‐reach distance test, but identified no statistically significant difference between the intervention and control group. Three studies assessed muscle strength (knee, ankle, back and leg, and inspiratory muscle strength). Only the back and leg strength combination score showed statistically significant differences on the muscle strength end‐score between the intervention and control group (SMD 1.41; 95% CI 0.71 to 2.11). Apart from one sub‐scale of the cancer scale (Worries; P value = 0.03), none of the health‐related quality of life scales showed a significant difference between both study groups on the end‐score. For the other outcomes of fatigue, level of daily activity, and adverse events (all assessed in one study), there were no statistically significant differences between the intervention and control group. None of the included studies evaluated activity energy expenditure, time spent on exercise, anxiety and depression, or self efficacy as an outcome. AUTHORS' CONCLUSIONS: The effects of physical exercise training interventions for childhood cancer participants are not yet convincing. Possible reasons are the small numbers of participants and insufficient study designs, but it can also be that this type of intervention is not as effective as in adult cancer patients. However, the first results show some positive effects on physical fitness in the intervention group compared to the control group. There were positive intervention effects for body composition, flexibility, cardiorespiratory fitness, muscle strength, and health‐related quality of life (cancer‐related items). These were measured by some assessment methods, but not all. However, the quality of the evidence was low and these positive effects were not found for the other assessed outcomes, such as fatigue, level of daily activity, and adverse events. There is a need for more studies with comparable aims and interventions, using a higher number of participants that also include diagnoses other than ALL.